Health Anxiety, Health Perception, and Healthy Lifestyle Behavior Among Psychiatric Patients During the COVİD-19 Pandemic - Korkmaz, Sevda; Ateşçelik, Metin; Balcı, Hale Nur; Baykara, Sema; Canpolat, Şeyda; Korkmaz, Hasan; Atmaca, Murad (Physicians Postgraduate Press Inc., 2022)
Objective: To compare the health anxiety and healthy lifestyle behavior experienced by psychiatric patients due to the coronavirus disease 2019 (COVID-19) pandemic with that of a control group. Methods: The study included 120 outpatients (aged 18–65 years) diagnosed with a psychiatric illness (DSM-5 criteria) who presented to a psychiatry outpatient clinic between June and August 2020. The control group included 120 healthy individuals with a similar age and sex distribution as the patient group. Data were collected with a questionnaire developed by the authors to determine the participants’ adherence to COVID-19 hygiene rules and associated behavioral norms. The Health Anxiety Scale–Short Form, Health Perception Scale, and Health-Promoting Lifestyle Profile were completed by all participants. Results: The mean Health Anxiety Scale score was significantly lower in the patient group compared to the control group (P <.01). Health anxiety was high in 8% of the patients and 32% of the controls. Also, the mean Health-Promoting Lifestyle Profile score was statistically significantly lower in the patient group compared to the control group (P <.01). There was no significant difference between the groups based on health perception scores and adherence to hygiene rules. Conclusions: As expected, the healthy lifestyle behavior of individuals without psychiatric illness was higher compared to those with mental disorders. However, health anxiety about COVID-19 was higher among healthy individuals compared to those with a psychiatric disorder. Thus, it could be suggested that individuals without a psychiatric illness prior to the pandemic could need psychiatric assistance after the pandemic. © 2022 Physicians Postgraduate Press, Inc.
Keywords: Anxiety; COVID-19; Depression; Healthy Lifestyle; Humans; Pandemics; Perception; SARS-CoV-2; adult; anxiety; anxiety disorder; Article; behavior assessment; controlled study; coronavirus disease 2019; COVID-19 Anxiety Scale; depression; DSM-5; fear; female; Health Anxiety Scale score; Health Perception Scale; Health Promoting Lifestyle Profile; healthy lifestyle; human; hygiene; Illness Perception Questionnaire; Likert scale; major clinical study; male; mental disease; mental disease assessment; mental health; mental patient; obsessive compulsive disorder; pandemic; perception; physical activity; questionnaire; sex ratio; smoking; social distancing; spiritual healing; stress management; anxiety; healthy lifestyle; pandemic; perception; psychology